PL.69 Delivery Outcomes and Events in Subsequent Pregnancies after Previous Anal Sphincter Injury. (26th April 2013) - Ali, AA; Glennon, KG; Yousif, SY; Eogan, ME
Abstract : Introduction: Few recent studies have examined outcome in pregnancies following previous third degree perineal tears and results are conflicting. One study found that although anal sphincter injury was increased five-fold at next delivery compared with all multiparae, 95% of women delivering vaginally after a previous third degree tear did not sustain further overt sphincter damage. (1). In this institution it is recommended that all women with a prior history of ASI are seen at a perineal clinic in the third trimester in subsequent pregnancies. Objective: To assess the mode of delivery following a previous anal sphincter injury (ASI) and to evaluate perineal outcome following vaginal birth. Methods: A retrospective search of the hospital PAS systems was conducted on patients who had a delivery following an ASI from 2010 – 2012. Variables were described by counts and percentages and analysed using SPSS version 20. Results: Between January 2010 and July 2012, 147 women with previous ASI were assessed in the third trimester regarding mode of delivery. The results highlight risk factors for ASI and summarise factors which influence decision for subsequent mode of delivery. Perineal outcomes are documented for those who delivered vaginally. Conclusion: This paper highlights the importance of individualised antenatal assessment in patients who have previously sustained ASI. Patients who have prior ASI may have a personal preference when considering mode of delivery, but a specialist clinic affords them opportunity for detailed discussion. Many women went on to have uncomplicated vaginal deliveries after previous ASI. Reference: Harkin R, Fitzpatrick M, O'Connell PR, et al . Anal sphincter disruption at vaginal delivery: is recurrence predictable? Eur J Obstet Gynecol Reprod Biol 2003;109: 149–52.